The tumorigenicity of multipotent adult germline stem cells (maGSCs) after transplantation into the heart is affected by natural killer cells and by cyclosporine A independent of its effects on lymphocytes - Hübscher, Daniela; Kaiser, Diana; Elsner, Leslie; Monecke, Sebastian; Dressel, Ralf; Guan, Kaomei (Frontiers in Immunology, 2017)
Transplantation of stem cells represents an upcoming therapy for many degenerative diseases. For clinical use, transplantation of pluripotent stem cell-derived cells should lead to integration of functional grafts without immune rejection or teratoma formation. Our previous studies showed that the risk of teratoma formation is highly influenced by the immune system of the recipients. In this study, we have observed a higher teratoma formation rate when undifferentiated so-called multipotent adult germline stem cells (maGSCs) were transplanted into the heart of T, B, and natural killer (NK) cell-deficient RAG2-/-γc-/- mice than in RAG2-/- mice, which still have NK cells. Notably, in both strains the teratoma formation rate was significantly reduced by the immunosuppressive drug cyclosporine A (CsA). Thus, CsA had a profound effect on teratoma formation independent of its immunosuppressive effects. The transplantation into RAG2-/- mice led to an activation of NK cells, which reached the maximum 14 days after transplantation and was not affected by CsA. The in vivo activated NK cells efficiently killed YAC-1 and also maGSC target cells. This NK cell activation was confirmed in C57BL/6 wild type mice whether treated with CsA or not. Sham operations in wild type mice indicated that the inflammatory response to open heart surgery rather than the transplantation of maGSCs activated the NK cell system. An activation of NK cells during the transplantation of stem cell-derived in vitro differentiated grafts might be clinically beneficial by reducing the risk of teratoma formation by residual pluripotent cells.